Pemeriksaan Perkara Dispensasi Kawin Oleh Hakim Tunggal Di PA Batang Perspektif Maslahah - Ahmad Zubaeri; Aizaturrohmah Aizaturrohmah; M. Khoirur Rofiq (Indonesia, 2022)
Applications for marriage dispensation at the Batang Religious Court (PA) are increasing, especially after the revision of the Marriage Law (Law Number 16 of 2019) which limits the minimum age for marriage to 19 years. The trial of marriage dispensation cases also changed with the existence of PERMA Number 05 of 2019 concerning Guidelines for Submitting Applications for Marriage Dispensations with a single judge. The aims of this research are examine the implementation of the marriage dispensation examination with single judge and it’s benefits in PA Batang. This research is a legal research with an empirical juridical approach, primary data in the form of information from the chairman and judges in PA Batang, data collection using semi-structured interviews, observations of marriage dispensations in PA Batang, and documentation of marriage dispensation decisions. This study resulted (1) the examination of the marriage dispensation case by single judge at PA Batang was in accordance with PERMA Number 05 of 2019, but did not involve TKSK as a child assistance institution because the community has difficulty in presenting TKSK and the still unfamiliar with the procedures for examining marriage dispensations. Alternatively, PA Batang brings village officials to testify in the case, (2) The benefits of examining a marriage dispensation case by a single judge in Batang PA are, the trial process can be completed quickly, the granting of a marriage dispensation permit can prevent violations of applicable norms, and as an effort to realize the benefit of maintaining religion, soul, mind, lineage or descendants.